PENDEKATAN PSIKOLOGI PENDIDIKAN ISLAM DALAM PEMBENTUKAN MORAL ANAK - Muchlisin, Imam; Habibi, Rohim (https://www.ejournal.smaamc.sch.id/index.php/belajar, 2023)
Children's character or morals do not appear suddenly without an educational process. One approach in children's character education is the application of religious education from an early age. This article discusses how children's character education can be done through Islamic and psychological approaches. The results of this research are as follows: Islam and Psychology have similar views and goals in interpreting character education in children. Basically, children should receive positive stimulation from an early age, because the early years of development are the foundation for the formation of one's personality and character. Children's character building can be started early by instilling moral concepts that are carried out consistently by parents as the main educators, followed by support from the school environment and society, the application and habituation of moral concepts are effective in preventing individuals from committing prohibited acts..